Ascariasis in the Gall Bladder - A Rare Case (Bangladesh Journal of Medical Science, 2014)
Settlement of adult form ascariasis parasite in the gall bladder is rare constituting 2.1 % of hepatobiliary ascariasis4. Radiologic imaging methods play an important role in the diagnosis of the parasite in the biliary tree. Computed tomography (CT), magnetic resonance imaging (MRI) and endoscopic retrograde cholangiopancreatography (ERCP) are used in the diagnosis of hepatobiliary ascariasis. However, ultrasonography is still the first method and most preferred due to its ease of applicability and the fact that it is inexpensive and non-invasive. We report a rare case of Ascariasis lumbricoides present in gall bladder. DOI: http://dx.doi.org/10.3329/bjms.v13i3.17740 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.343-344